The Impact of Contractor Safety Leadership on Workers Safety Behavior - Andi Andi; Stephen Hans Sumali; Giovanni Ferdinand Limansantoso (Civil Engineering Dimension, 2022)
The importance of safety leadership for effective management of safety behavior has been acknowledged by many researches. However, its development in construction industry is lagging compared to other industry, especially in Indonesia. This research empirically evaluates the impact of contractors’ safety leadership on construction workers’ safety behavior. It explores three dimensions of safety leadership variable and two dimensions of safety behavior variable, and then examines the relationship between the two variables. Data was gathered through questionnaire survey to eighty-four workers from five on-going construction projects in Surabaya. Multiple regression analysis was performed to examine two models of the impact of safety leadership on safety behavior. The findings suggest that safety concern and safety motivation positively impact safety compliance and safety participation, whilst safety policy only have a significant positive impact on safety participation. The paper discusses these findings and their implications for shaping workers’ safety behavior in construction projects.